Power Savings in Cold Storage - Arslan, Şuayb Şefik; Göker, Turguy (My University, 2016)
Methods and apparatus associated with data cold storage are described. Example apparatus include an array of data storage devices arranged in rows and columns. Columns of the array are orthogonal to rows. A row has an associated row-centric power supply, and a column has an associated column-centric local electronics module (LEM) that controls a data storage device in the column independently of other data storage devices in the array. Example apparatus include logics that control a power mode of a data storage device independently of other data storage devices in the array, that control a power mode of an LEM, that adaptively regulate the level of data stored in a buffer, and that determine whether a data object will be stored in the buffer or stored on a data storage device in the array, based on the probability the data object will be accessed within a threshold period of time.